Analisis semiotika John Fiske: Pengorbanan Generasi Sandwich dalam Film Home Sweet Loan - Leni Listiana; Anisti Anisti; Tuty Mutiah (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The sandwich generation is a productive age group that is crushed in dual responsibilities, namely caring for parents and children simultaneously, both emotionally and financially. This study aims to determine and analyze the meaning of sacrifice experienced by the sandwich generation in the film Home Sweet Loan using semiotic analysis techniques developed by John Fiske. This movie was chosen because it can illustrate the social reality of Indonesian society, especially in the context of family culture. The analysis found that the sacrifice of Kaluna, the main subject of the research, depicts economic pressure, role conflict in the family, and inequality of social responsibility. This research uses descriptive qualitative method and John Fiske's semiotic analysis, which includes three levels of meaning of reality, representation, and ideology. The scenes in the movie show how the sandwich generation faces the problems of limited space, loss of personal comfort, and having to postpone their desires for family needs. The analysis shows that movies as popular media have the power to shape collective consciousness regarding social issues, especially regarding the injustices faced by the sandwich generation. It is hoped that this research will help media research, especially how movies as popular media reflect social issues and form collective consciousness.